Efficient Production of Recombinant Protegrin-1 From Pichia pastoris, and Its Antimicrobial and in vitro Cell Migration Activity - Huynh, Evanna; Akhtar, Nadeem; Li, Julang (Frontiers in Microbiology, 2018)
Protegrin (PG) belongs to the antimicrobial peptide (AMP) cathelicidin family. To date, five protegrin sequences have been identified in pigs, PG-1 to PG-5. Of these, PG-1 exhibits potent antimicrobial activity against a broad range of antibiotic-resistant microorganisms as well as viruses. However, the other potential role(s) of PG beyond antimicrobial has largely been unexplored. The aim of this study was to use nonpathogenic yeast Pichia pastoris to express antmicrobially active recombinant protegrin (rPG-1). Additionally, the effect of PG-1 on cell migration and proliferation was also examined in vitro using pig intestinal epithelial cells as a model. Highest level of rPG-1 (104 ± 11 μg/mL) was detected at 24 h in fermentation culture medium. Similar to rPG-1, 0.8 ± 0.10 g/L of proform PG-1 (rProPG-1) and 0.2 ± 0.02 g/L of the PG-1 cathelin domain (rCath) was detected in fermentation culture medium. Resulting recombinant PG-1 and cleaved rProPG-1 exerted antimicrobial activity against Escherichia coli DH5α at the same level as chemically synthesized PG-1. Enhanced cell migration was observed (p< 0.05) in groups treated with rProPG-1, rCath, and rPG-1 compared to the control. Furthermore, rPG-1 was stable at temperatures ranging from 25°C to 80°C. In summary, biologically active recombinant protegrin in its pro-, cathelin- and mature- forms were successfully expressed in P. pastoris suggesting potential feasibility for future therapeutic applications.